Zingiber cassumunar Roxb. (Bangle), Guazuma ulmifolia Lamk. (Jati belanda), and Murraya paniculata (Kemuning) have been used as slimming agents in jamu. A few researches have performed studies on their potency as antiobesity. The aim of this research was to investigate the potency of Z. cassumunar rhizome, G. ulmifolia, and M. paniculata leaf extracts as antiobesity agent based on in vitro inhibition activity of the extracts on pancreatic lipase activity. In this research, water content determin - DYAH ISWANTINI; RHOITO FROISTA SILITONGA; ELIZABETH MARTATILOFA; LATIFAH KOSIM DARUSMAN (Bogor Agricultural University, Indonesia, 2011)
Zingiber cassumunar Roxb. (Bangle), Guazuma ulmifolia Lamk. (Jati belanda), and Murraya paniculata (Kemuning) have been used as slimming agents in jamu. A few researches have performed studies on their potency as antiobesity. The aim of this research was to investigate the potency of Z. cassumunar rhizome, G. ulmifolia, and M. paniculata leaf extracts as antiobesity agent based on in vitro inhibition activity of the extracts on pancreatic lipase activity. In this research, water content determination, phytochemical assay, toxicity assay and in vitro assay of inhibition activity on pancreatic lipase were performed toward single and mixture extracts of Z. cassumunar, G. ulmifolia, and M. paniculata resulted by water, ethanol, and saponin extractions. The results indicated that 100 ppm of ethanol extraction of Z. cassumunar had highest inhibition effect on the activity of pancreatic lipase (29.17%), followed by 100 ppm of water extraction of M. paniculata (25.66%), 60 ppm of ethanol extraction of G. ulmifolia leaves (25.13%) and ethanol extraction mixture of Z. cassumunar, G. ulmifolia, and M. paniculata leaves with ratio of 25:25:25 (21.58%). These inhibition effects were higher than inhibitory effect of 100 ppm of Xenical®/orlistat as the positive control, with the inhibition value of 17.53%. Saponin crude extracts had lower inhibitory effect than the other extractions. It was suggested that ethanol extraction of Z. cassumunar, and G. ulmifolia and water extraction of M. paniculata had potency as antiobesity agent